The They and Average Everydayness: A Heideggerian Approach to Virginia Woolf’s The Waves - Hakan YILMAZ (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2018)
The work of Virginia Woolf has been deemed exemplary in modernist fiction with its unyielding representations of highly self-conscious individuals. This is especially the case with her perhaps most inaccessible work The Waves (1931) in which six characters are presented as having quite self-aware and contrasting personalities. Accordingly, much attention has been paid to their peculiar and differentiating traits that set them apart from each other. Drawing upon the phenomenological insights provided by Martin Heidegger’s philosophy, this paper argues that there is a more primordial layer beneath the seemingly clashing natures of these characters in The Waves that binds them to each other, and that a close examination of the intersubjective relations between the characters (i.e. the self and others) reveals them to be not that different from each other on the ontological level. Resorting to the conceptual tools such as average everydayness, “the they,” and being-at-home that Heidegger proposes in Being and Time (1927), this paper discusses how, ontologically speaking, the characters in The Waves, for the most part, are lost (or at times try hard to be lost) among each other.